Sosialisasi Komponen Kondisi Fisik Pada Cabang Olahraga Bulutangkis pada Mahasiswa Pendidikan Jasmani - Ma'arif, Ilmul; Setyawan, Risfandi; Prasetyo, Guntum Budi (UIR Press, 2024)
This form of service activity is carried out based on the need for student understanding of the components of badminton physical condition and applying the form of physical condition training in badminton, physical condition is a form of overall description related to the fitness of the human body and can also produce energy and be able to carry out every activity in sports optimally. In this service has a goal in this case students will have an understanding and knowledge related to the components of physical conditions and forms of training in badminton sports and the methods used are lectures and questions and answers, demonstrations and practices. The form of this activity includes preparing the material that will be conveyed in the activity, the implementation of this activity by delivering explanations related to the components of physical conditions and forms of training with field practice. Evaluation summarises events in activities related to the situation and input for these activities, the conclusion of this activity is that students get good benefits as well as understanding and knowledge of the components of physical conditions and forms of training in badminton.